2004
DOI: 10.4314/sajas.v34i1.4040
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the body composition, carcass characteristics and retail cuts of South African Mutton Merino and Dormer sheepe/pj

Abstract: The body composition, carcass characteristics and retail cuts of 61 Dormers (21 rams and 40 ewes) and 35 South African Mutton Merinos (SAMM) (17 rams and 18 ewes) were determined. A range of carcass measurements was recorded. Since there was no sex x breed interaction, only main effects of breed and sex were considered. There were no differences in slaughter weight between Dormer and SAMM sheep at 18 months of age. Dormers had a 2.7% point higher dressing percentage and a 6.2% higher carcass weight than the SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
4
13
1
2
Order By: Relevance
“…The dressing percentage results obtained from the present study are similar to those previously recorded for sub-adult male impala (57.0%-59.2%) [16]. The mean pooled warm dressing percentage of male and female impala (57.4%) from the present study is higher than the dressing percentages of domestic livestock, which has been reported to range from 50.3% to 53.8% for cattle [32] and 41.5% to 44.2% for sheep [33]. In combination with the lack of visible subcutaneous fat in impala, these high dressing percentages are indicative of higher lean meat production potential in impala.…”
Section: Carcass and Offal Yieldssupporting
confidence: 89%
“…The dressing percentage results obtained from the present study are similar to those previously recorded for sub-adult male impala (57.0%-59.2%) [16]. The mean pooled warm dressing percentage of male and female impala (57.4%) from the present study is higher than the dressing percentages of domestic livestock, which has been reported to range from 50.3% to 53.8% for cattle [32] and 41.5% to 44.2% for sheep [33]. In combination with the lack of visible subcutaneous fat in impala, these high dressing percentages are indicative of higher lean meat production potential in impala.…”
Section: Carcass and Offal Yieldssupporting
confidence: 89%
“…In addition, the presence of fatty acids heneicosanoic acid could oxidize omega fatty acids, but the exact mechanism is still unknown. The results of this study indicate that the marbling fat content of garut sheep was 1.60% -1.73%, lower than other sheep breeds such as south african mutton, merino, dormer (Cloete et al, 2004), moranda nova, santa inez and crosses dorper x santa inez (Costa et al, 2009) as well as cholesterol content (6.10% -8.91%) was lower than reported Costa et al (2009) and Mas'ud (2012). It is suspected due to the age of the sheep were used relatively young (8-10 months), where the deposition of marbling not yet formed perfectly.…”
Section: Association Of Polymorphisms Lipoprotein Lipase Gene C 192 contrasting
confidence: 49%
“…LPL leads to increased oxidation Oleic was most abundant fatty acid in this study, followed by palmitic, stearic, myristic, palmitoleic and linoleic. Several studies have reported that oleic is the major fatty acid was found in sheep (Cloete et al, 2004;Costa et al, 2009;Gallardo et al, 2011;Borys et al, 2012;Popova, 2014). Oleic acid is formed by stearic acid by activity of stearoyl CoA desaturase (Wood et al, 2008).…”
Section: Association Of Polymorphisms Lipoprotein Lipase Gene C 192 mentioning
confidence: 98%
“…Cloete et al (2007) found that the SCF depth of Dorper lambs slaughtered at 43 kg was ~2.16 mm, while crossbred lambs from SAMM and Merino sires had a significantly thinner fat depth. The SAMM breed tends to deposit SCF at a relatively slower rate (Neser et al, 2000;Cloete et al 2004) than the early maturing Dorper breed. The Merino is a leaner and later maturing breed, and so would deposit fat at a slower rate than other meat sheep breeds.…”
Section: Discussionmentioning
confidence: 99%